Audit, Fiscal, and Capital Expenditure: Determinants of Local Government Corruption - Evelyn Christina Br Saraghi; Hari Setiyawati (Publikasi Indonesia, 2025)
Corruption remains a prevalent issue that can manifest at all tiers of government, including regional government in Indonesia. This research aims to empirically prove the impact of audit opinions, audit findings, fiscal decentralization, and capital expenditures on corruption within local government entities. In this study, the level of corruption is quantified using cases of regional government corruption that have received a final legal decision from the court. This research employs a quantitative methodology utilizing panel data regression analysis. The research population consists of all regency/municipality governments in Indonesia during the fiscal year period from 2018 to 2022. The sample was obtained using purposive sampling, yielding 219 regional governments which met the criteria. Over a five-year observation period, 1,095 observations were analyzed. The data was then processed and analyzed using Eviews version 12. The research results show that audit opinion and fiscal decentralization significantly reduce local government corruption. Higher audit quality and fiscal decentralization correlate with lower levels of corruption. Meanwhile, audit findings and capital expenditures have no effect on local government corruption.